Indigenous Knowledge Systems in India: Exploring Legal Pluralism, Constitutional Protection, and Cultural Heritage Preservation Strategies - Amit Kumar (SocioHumania: Journal of Social Humanities Studies, 2026)
This study examines the relationship between Indigenous Knowledge Systems (IKS) and legal autonomy within the Indian legal and constitutional framework. It explores how ancient Indian governance recognized legal pluralism through customary laws, village autonomy, tribal jurisdictions, and decentralized judicial systems. The study further analyzes the ecological and philosophical foundations of Indigenous Knowledge Systems, emphasizing the indigenous worldview that promotes harmony between humans and nature through principles of sustainability and environmental stewardship. Additionally, the research evaluates the legal challenges faced by indigenous communities under modern intellectual property regimes, particularly concerning communal ownership, oral traditions, and biopiracy. Constitutional protections such as the Fifth Schedule, Sixth Schedule, and the Forest Rights Act (2006), alongside landmark judicial decisions, demonstrate India’s efforts to safeguard indigenous rights and traditional knowledge. The study also highlights international legal mechanisms, including the Convention on Biological Diversity (CBD), the Nagoya Protocol, and WIPO initiatives, while emphasizing the need for stronger legal frameworks and international cooperation to ensure indigenous sovereignty and long-term protection of Indigenous